Effect of previous unilateral injuries on ground reaction force bilateral assymmetries during static lifting and standing - Rocheford, E. C.; deVoe, D. E.; Reiser, R. F. (Journal of Human Movement Studies, 2006)
Due to fluctuating asymmetries, functional asymmetries may be expected during Symmetrie tasks. The presence of a unilateral injury may increase the level of asymmetry. However, after recovery, it is not clear if a person would be more asymmetric than the general population. The goal of this investigation was to assess bilateral vertical ground reaction forces during quiet stance and a maximum effort static leg lift in a group of workers (firefighters) either with a previous unilateral injury (PUI, n=-22) or without (NPUI, n=\7). Quiet stance was assessed over a single five second period. The leg lift was performed by pulling up on a chain-restrained hand hold adjusted to be slightly above knee level. The highest one second of three, three second maximal efforts was analysed. All subjects except for one in each group favored one side of the body while lifting (different from 50.0/50.0%) and all favored one side during Standing. Levels of asymmetry were not different between groups in either condition (p>0.05). However, PUI subjects were significantly more asymmetric while Standing compared to lifting (p=0.005) while NPUI subjects were not (p=0.301). NPUI subjects produced significantly greater forces under their non-kicking leg while lifting (p=0.029) while PUI subjects did not (p=0.124). Both differences were on the order of 1-2%. Additional limitations related to subject categorisation and the use of quiet stance and the static leg lift äs appropriate assessors of asymmetry place caution on the practicality of the findings. However, due to the widespread implications for asymmetries to affect both performance and injury, the results are an important starting point for further investigation.